Carbon microelectrodes for the measurement of neurotransmitters with fast-scan cyclic voltammetry: methodology and applications - Alyamni, Nadiah; Abot, Jandro L.; Zestos, Alexander G. (Frontiers in Bioengineering and Biotechnology, 2025)
Carbon microelectrodes (CMEs) have emerged as pivotal tools in the field of neurochemical sensing, enabling precise, real-time monitoring of neurotransmitters in both research and clinical contexts. The current review explores the design, fabrication, and application of CMEs, emphasizing recent advancements in material science and electrochemical techniques that enhance their sensitivity, selectivity, and biocompatibility. Innovations such as the incorporation of nanomaterials, including graphene and carbon nanotubes, and the adoption of advanced fabrication methods like three-dimensional (3D) printing and chemical vapor deposition, are discussed in detail. These developments have led to significant improvements in electrode performance, the reduction of biofouling and interferants, while enabling the detection of low concentrations of neurochemicals in complex biological systems. This review further highlights the potential of CMEs to address clinical challenges such as diagnosing and monitoring neurological disorders such as Parkinson’s Disease and depression. By integrating advanced surface modifications, polymer coatings, and method development strategies, CMEs demonstrate high durability, reduced fouling, and enhanced specificity. Despite these advancements, challenges remain related to long-term in vivo stability, batch fabrication, and reproducibility, thus necessitating further research and optimization. This review highlights the transformative potential of CMEs in both research and therapeutic applications, providing a comprehensive overview of their current state and future directions. By addressing existing limitations and leveraging emerging technologies, CMEs have the potential to further enhance neurochemical sensing and contribute to breakthroughs in neuroscience and biomedical science.